The Impact of Immigration on Wage Dynamics: Evidence from the Algerian Independence War - Anthony Edo (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates the dynamics of wage adjustment to an exogenous increase in labor supply by exploiting the sudden and unexpected inflow of repatriates to France created by the independence of Algeria in 1962. I track the impact of this particular supply shift on the average wage of pre-existing native workers across French regions in 1962, 1968 and 1976. I find that regional wages decline between 1962 and 1968, before returning to their pre-shock level 15 years after. While regional wages recovered, this particular supply shock had persistent distributional effects. By increasing the relative supply of high educated workers, the inflow of repatriates contributed to the reduction of wage inequality between high and low educated native workers over the whole period considered (1962-1976).
Keywords: F22; J21; J61; 330; labor supply shock; wages; immigration; natural experiment